2011
DOI: 10.3168/jds.2010-3871
|View full text |Cite
|
Sign up to set email alerts
|

Hay intake improves performance and rumen development of calves fed higher quantities of milk

Abstract: Research to date has suggested that access to forage before weaning can limit rumen development in calves, but no research has yet addressed the role of forage for calves fed higher quantities of milk. This study compared performance and rumen development of calves provided high volumes (equivalent to approximately 20% of calf birth weight) of milk with and without access to hay. At d 3 of age, individually housed calves were randomly assigned to treatment (either ad libitum access to chopped grass hay or no f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

41
232
4
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 228 publications
(284 citation statements)
references
References 38 publications
(52 reference statements)
41
232
4
7
Order By: Relevance
“…This is consistent with reports by Baldwin and Jesse [22] and Khan et al [9], who revealed that calves and lambs do not consume signifi cant quantities of solid feed before two weeks of age. The rumen starter intake observed in kids in our study is similar to that reported by Luo et al [23] in Spanish kid goats at 5-6 weeks of age (21.7 g DM d -1 ).…”
Section: Intake and Growth Of Kids According To Age And Rearing Systemsupporting
confidence: 82%
See 4 more Smart Citations
“…This is consistent with reports by Baldwin and Jesse [22] and Khan et al [9], who revealed that calves and lambs do not consume signifi cant quantities of solid feed before two weeks of age. The rumen starter intake observed in kids in our study is similar to that reported by Luo et al [23] in Spanish kid goats at 5-6 weeks of age (21.7 g DM d -1 ).…”
Section: Intake and Growth Of Kids According To Age And Rearing Systemsupporting
confidence: 82%
“…The higher ration intake of AR kids compared to TR kids indicates that the alternative rearing system with weaning at 30 days of age encouraged earlier consumption of solid food. This is because there is an inverse relationship between the intake of milk and solid feed consumption [9,24,25]. Therefore, when milk supply is reduced or stopped the intake of solid feed increases signifi cantly [9,26].…”
Section: Intake and Growth Of Kids According To Age And Rearing Systemmentioning
confidence: 99%
See 3 more Smart Citations